Short‐term and long‐term effects of excessive consumption of saturated fats and/or sucrose on metabolic variables in Sprague Dawley rats: a pilot study. (4th July 2013) - Pranprawit, Araya; Wolber, Frances M; Heyes, Julian A; Molan, Abdul L; Kruger, Marlena C
Abstract: BACKGROUND: Feeding high‐fat and/or high‐sugar diets to rats leads to a change in markers of metabolic syndrome. However, types and amounts of fat and sugar as well as the length of the experiment for establishing diet‐induced metabolic syndrome in the Sprague Dawley (SD) rat model remain uncertain. This study was designed to investigate the effects in SD rats of consuming excess lard, sucrose or a combination of lard and sucrose for a short (4 week) or long (8 week) period of time . RESULTS: Consumption of the high‐fat high‐sugar (HFHS) diet significantly increased weight gain and abdominal fat weights ( P < 0.05), and the rats also began to develop signs of impaired glucose tolerance and had increased fasting blood lipids glucose and insulin concentrations. The high‐fat (HF) diet mainly affected weight gain and fat deposition, whereas the high‐sugar (HS) diet induced glucose intolerance but not the obesity‐related parameters. Control rats showed a tendency towards insulin resistance and glucose intolerance when fed for a long‐term period . CONCLUSION: The lard plus sucrose‐based HFHS diet is the most efficient one for inducing signs of metabolic syndrome, and SD rats fed this diet for 8 weeks successfully develop obesity and insulin resistance, which can be used as a model for metabolic syndrome research. © 2013 Society of Chemical Industry